Nb, Se-codoped ZnIn2S4/NbSe2 composites with enhanced catalytic activity and photodegradation performance towards tetracycline. (6th March 2023) - Zhao, Xianhui; Huang, Fei; Li, Dengke; Yan, Aihua; Zhang, Tongyang; Zhao, Wenxue; Gao, Ye; Zhang, Jixu
Abstract: Low quantum efficiency and serious photogenerated carrier recombination have been urgent bottleneck problems for photocatalytic materials. Herein, we prepared Nb, Se-codoped ZnIn2 S4 /NbSe2 composites through a facile solvothermal method. The synergetic effect of codoping and cocatalyst was investigated on the photodegradation performance towards tetracycline under visible-light irradiation. By adjusting the final composition, the comprehensive characterization revealed that the optimum degradation efficiency of NS/ZIS-1.6 catalyst arrived at 75% in 70 min, which was 5.8 times higher than that of pure ZnIn2 S4 . Deep analysis indicated that the enhanced photocatalytic performance could be attributed to higher light absorption, more efficient electron/hole separation, faster charge transport, and lower carrier recombination. This work may offer novel viewpoint for design of high-performance catalysts towards the visible-light-driven photodegradation system.